PROBLEMATIKA KONTEMPORER PEREMPUAN DALAM PERKAWINAN DAN KELUARGA MENURUT HUKUM ISLAM - Abd. Wahab Abd. Muhaimin (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2010)
According to Islamic law, marriage aims at creating a harmonious and affectionate family. Unfortunately, some problems often appear within marriages that frequently result in disagreement and dispute among the couples, which sometimes trigger domestic violence. These occur because some couples do not abide Islamic laws available to them. Key word: Mariage, Trigger Domestic Violence, KDRT